UPAYA ASEAN DALAM MENGHADAPI SKEMA LIBERALISASI E-COMMERCE DI ASEAN-6 (2015 – 2017) - Miftah Rahman (Review of International Relations, 2020)
This study discusses about digital era marked by the advancement of knowledge and innovation in the field of Technology, Information and Communication (ICT) which has provided major changes to all aspects of life, especially in economy. ASEAN as a regional cooperation in the Southeast Asia region, currently as an emerging market in e-commerce competition, especially for Singapore, Malaysia, Thailand, Indonesia, the Philippines and Vietnam (ASEAN-6). Based on this phenomenon, my research question is, how are ASEAN-6's efforts in facing of e-commerce liberalization in the digital era in line with the ASEAN framework (AEC Blueprint 2015 & 2025, ASEAN ICT Masterplan and ASEAN Digital Integration). This research use the theory of trade liberalization, the concept of economic integration and the concept of digital economics to be able to examine the phenomenon of e-commerce liberalization in ASEAN-6. The various literature reviewed by the author shows that the growth of e-commerce is influenced by four factors, namely: 1) internet infrastructure; 2) electronic payment system; 3) shipping services that has a wide coverage; 4) government policy framework in each ASEAN-6 country. In addition, there are several obstacles found including: 1) the geographical location of each ASEAN-6 country that affects the process of developing the internet infrastructure; 2) issues of personal data protection and cyber security related to electronic payment systems; 3) effectiveness and efficiency of the existence of shipping services, especially shipping between countries; and 4) policy discrepancies between countries. This study concludes that as a regional organization in Southeast Asia, ASEAN continues to strive to harmonize regulations among member countries, form a framework of cooperation and other agendas to be able to harmonize the development of ICT, especially the growth of e-commerce. The fundamental difference from this study with previous studies is that there have been no studies that examine e-commerce liberalization in the ASEAN region, so the author tries to collaborate on several facts related to the growth of e-commerce liberalization in ASEAN-6 Keywords: ASEAN, e-commerce, digital economy, economic integration